LITERARY MIRACLE OF THE QURAN - Ahmad, Meraj (UIN Ar-Raniry, 2016)
The literary inimitability of the Holy Quran and its wisdom, it’s rhythmical and phonetically excellence, in its perfect meanings, in its unmatched literary styles and its perfect grammatical structure has been discussed thorough out the Islamic History. The most important point of Quran’s miracle which means the words and expressions applied in Quran are arranged in a very specific and precise way that any movement changes the meaning. The Quran’s challenges everyone mostly to make only one verse in terms of rhetoric and eloquence like Quran, So far no one has surmounted this challenge. The Quran is neither prose nor poem while majority of the words are either prose or poems. It is not poem on the ground that it doesn’t have the basic elements of rhyme. In addition to rhyme another element of poem is imagination which is not applied in Quran and the words in it are imagination free. The Quran indeed contains an ocean of information relating to a wide variety of subjects. They include: religious and moral guidance, lessons from the lives of the peoples of the past, the message of the Prophets and Messengers of Allah, the physical sciences and historical accounts of important events. But all of this is delivered with the most fantastic literary rhythm and excellence. The Quran achieved this unique literary form by fusing together metrical and non-metrical speech. This fusion of metrical and non-metrical composition is present throughout the whole of the Quran and cannot be found in any Arabic text, past or present. The aim of this paper is to study three basic aspects that have been propounded by scholars including literary, linguistic, and scientific miraculousness. The paper also highlights the literary miracles of the Holy Quran as well as rediscover it uniqueness in modern age. A full understanding of its merit as a literary masterpiece requires a fresh approach to the study of the scriptures that present the literary beauty of the Quran in the most precise and coherent fashion.